Management of Urinary Incontinence in Complete Bladder Duplication by Injection of Bulking Agent at Bladder Neck Level into the Proximal Urethra - Reza Khorramirouz; Seyedeh Sanam Ladi Seyedian; Sorena Keihani; Abdol-Mohammad Kajbafzadeh (Case Reports in Surgery)
Bladder duplication is a rare entity in children. The term encompasses a wide spectrum of anomalies from isolated bladder duplication in coronal or sagittal planes to duplicated bladder exstrophy and associated musculoskeletal and visceral anomalies. Given this wide variability, the treatment of these patients is not standardized. We hereby present a female patient with chief complaint of long-standing urinary incontinence who had complete bladder and urethral duplication and pubic diastasis. The patient was treated with bulking agent injection at the incompetent bladder neck and proximal urethra with resolution of incontinence, obviating the need for extensive surgeries.